PERAWATAN GINGIVITIS PADA ANAK PENDERITA HEMOFILIA-A - Budirahardjo, Roedy (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
Hemophilia is hereditary abnormal blood coagulation. It occurs in male children and recessive x-linked. Approximately, 80% of cases is hemophilia A that occurs because of factor VII deficiency. Hemophilia sufferers may get spontaneous bleeding on the gingival with inflammation (gingivitis). Therefore, it is important to maintain the gingival health. Dental cleaning procedure uses soft toothbrush and brushing with Bass technique. Gingivitis treatment in children uses scaling to achieve clean and delicate tooth surface. This treatment is initiated by antifibrinolytic medicine administration, antimicrobial medicine which may be administered on severe gingivitis case is metronidazole combined with penicillin or erythromycin. This sufferer has contra indication to antiplatelet medicine, analgesic such as aspirin and NSAID and acetaminophen.